Neglected tropical diseases: diagnosis, clinical management, treatment and control (Swiss Medical Weekly, 2012)
Branded in 2005, “neglected tropical diseases” have gained traction in terms of advocacy, interest for research, enhanced funding and political will for their control and eventual elimination. Starting with an initial set of 13 neglected tropical diseases – seven helminth, three bacterial and three protozoal infections – the list considerably expanded to more than 40 diseases that now also includes viral, fungal and ectoparasitic infections. In this review, we provide a comprehensive overview of the neglected tropical diseases, their causative agents and the current geographical distribution, including their importance for the general practitioners seeing returning travellers and migrants in Switzerland. We characterise the most important of the neglected tropical diseases in terms of at-risk population, estimated number of infections, annual mortality rates and global burden, including current knowledge gaps. With an emphasis on neglected tropical diseases due to helminths, protozoa and ectoparasites, we review common diagnostic methods and current recommendations for treatment at the population level and the individual patient, thereby juxtaposing the situation in highly endemic countries on one side, with Switzerland on the other. We highlight the clinical presentation and management of the neglected tropical diseases in general and then elaborate on two examples, strongyloidiasis and leptospirosis. Our review provides a global perspective of neglected tropical diseases and we hope that it will prove useful for the general practitioner and clinician in Switzerland and elsewhere to enhance their suspicion index, differential diagnosis, clinical management and treatment, including referral to specialised clinics and laboratories when need be.